Photoinduced Viscosity Changes of Polyesters Containing ortho-Hydroxyazo Groups - Girijan, K.R.; Sreejith, P.; Purushothaman, E. (Asian Journal of Chemistry, 2012)
The synthesis and photoinduced changes in viscosity of polyesters having ortho-hydroxyazo groups in the polymer backbone are described. Reversible photodecrease in viscosity was observed in all cases. Isomerization from trans to cis form is responsible for the photodecrease in viscosity. The extended conformation in the trans form changes to the more compact cis form upon irradiation results in ultimate decrease in viscosity.